2015
DOI: 10.1242/bio.012252
|View full text |Cite
|
Sign up to set email alerts
|

Id2 deletion attenuates Apc-deficient ileal tumor formation

Abstract: The expression level of inhibitor of DNA binding 2 (Id2) is increased in colorectal carcinomas and is positively correlated with poor prognosis. However, the functional significance of Id2 in intestinal tumorigenesis has not been fully defined using genetic approaches. Here, we show that Id2 promotes ileal tumor initiation in Apc-deficient mice. Expression of Id2 was stimulated by Wnt signaling through the enhancer region of the Id2 promoter at the early stage of tumorigenesis in Apc+/Δ716 (ApcΔ716) mice. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…APC mutation occurs in most human colorectal cancers. We recently reported that Id2 is involved in the tumor initiation process, and Id2 deficiency does not promote carcinogenesis of intestinal adenoma induced by Apc gene mutation ( 43 ). In addition, we observed no carcinoma development until 20 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…APC mutation occurs in most human colorectal cancers. We recently reported that Id2 is involved in the tumor initiation process, and Id2 deficiency does not promote carcinogenesis of intestinal adenoma induced by Apc gene mutation ( 43 ). In addition, we observed no carcinoma development until 20 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…MAX dimerization protein 1 (MXD1) belongs to the MAX dimerization protein family of proteins, which function as potent antagonists of c-Myc (Thomas et al, 2015). MXD1 contributes to tumor initiation in various tissues (Biyajima et al, 2015). However, the roles of MXD1 in lung cancer remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…2E). Gene sets associated with upregulation of ID1 and ID2, HLH factors that counteract E protein activity and increase stemness in intestinal homeostasis and cancer 40,[88][89][90][91][92][93] , were not enriched. These data demonstrated a strong induction of E protein-mediated transcription in the absence of repression by MTG16.…”
Section: Mtg16 Is Required For Attenuation Of E Protein Activity In the Colonmentioning
confidence: 99%
“…2E, Table S3). Gene sets associated with upregulation of Id1 and Id2, which counteract E protein activity and increase stemness in colon cancer (23,(49)(50)(51)(52), were not enriched (Fig. 2E).…”
Section: Mtg16-driven Goblet Cell Differentiation Is Dependent On Its...mentioning
confidence: 99%